Changes in prehistoric food cultures in Finland and North Norway: Examining the absorbed organic residues found in archaeological pottery - Pääkkönen, Mirva (fi=Turun yliopisto|en=University of Turku|, 2023)
During the prehistoric period, groups in the northern areas used unglazed ceramic vessels to store and prepare their food. This action left both visible and invisible residues on the walls of the ceramic vessels used. The current multidisciplinary study focuses on the invisible organic residues absorbed in the walls of ceramic vessels and uses organic chemistry methodology to study the changes that occurred in prehistoric food procurement patterns. To detect changes in the food culture, organic residues from archaeological pottery from Finland and North Norway are studied. To create reference values from Finland and the Baltic Sea, compound-specific stable carbon isotope values for the palmitic and stearic acids from modern mammalian tissue, ruminant milk, and fish are presented. Hunting and gathering was undertaken during the Comb Ware period in South Finland. In this study, the first evidence of dairy farming was found from Corded Ware vessels. Agriculture was less common during the Kiukainen Ware period, as residues of dairy fats were found only from one Kiukainen Ware vessel. Based on the results obtained for this thesis, agriculture intensified again during the Early Metal Period, as nearly half of the studied Morby vessels were found to have been used for storing or processing dairy products. Even after agricultural practises arrived in Finland, hunting and gathering remained still an important part of the food procurement cycle. During the Early Metal Period, groups using Risvik Pottery in North Norway were practising farming, but also utilising the marine environment as a food source. The hunter-gatherer groups in the coastal areas of the Norwegian Sea also based their diet mainly on fish and marine mammals. The groups inland in North Norway and Finland, however, had a more diverse food procurement pattern that consisted of terrestrial animals and fresh water fish. Together with the previous knowledge, the findings presented in this thesis shed more light on the food procurement patterns of the prehistoric groups that were living in the North.

Ruokakulttuurin muutokset esihistoriallisessa Suomessa ja Norjassa. Tutkimus arkeologiseen keramiikkaan imeytyneistä orgaanisista jäänteistä Ruoan valmistus ja säilytys lasittamattomassa keramiikka-astiassa jättää astian pintaan sekä näkyviä että näkymättömiä jälkiä. Tässä väitöskirjassa selvitetään orgaanisen kemian metodeja apuna käyttäen esihistoriallisten keramiikka-astioiden seinämiin imeytyneitä orgaanisia jäänteitä. Ruokakulttuurin muutosta selvitetään tutkimalla Etelä- ja Pohjois-Suomesta sekä Pohjois-Norjasta arkeologisilta kaivauksilta löytynyttä esihistoriallista keramiikkaa. Lisäksi tässä tutkimuksessa selvitetään Suomesta ja Itämerestä peräisin olevien nisäkkäiden, maidon ja kalojen palmitiini- ja steariinihappojen yhdistekohtaisten hiilen stabiilien isotooppien arvoja. Näitä arvoja voidaan tulevaisuudessa käyttää verrokkiaineistona tutkittaessa arkeologisen materiaalin isotooppiarvoja. Kampakeraamisena aikana ravinto hankittiin metsästämällä ja keräilemällä. Tässä tutkimuksessa varhaisimmat todisteet maitotaloudesta Etelä-Suomessa löytyvät nuorakeraamisista astioista. Kiukaisten kulttuurin aikaan maatalous ei ollut yhtä yleistä kuin nuorakeraamisena aikana. On kuitenkin todennäköistä, että maataloutta harjoitettiin Etelä-Suomessa pienimuotoisesti myös Kiukaisten kulttuurin aikana. Tutkituista Morbyn kulttuurin astioista lähes joka toisesta löydettiin merkkejä maitotuotteiden käsittelystä tai säilytyksestä. Tämän perusteella voidaan todeta, että varhaismetallikauden aikana maatalous yleistyi Etelä-Suomessa uudelleen. Pohjois-Norjassa varhaismetallikaudella Risvik-keramiikkaa käyttävät ryhmät harjoittivat maataloutta, mutta samanaikaisesti merenelävien osuus ruokavaliosta oli merkittävä. Myös Norjan rannikolla elävät metsästäjä-keräilijäyhteisöt hyödynsivät merenantimia suurissa määrin. Pohjois-Norjan ja Pohjois-Suomen sisämaassa asuvat ryhmät puolestaan käyttivät ravintonaan maanisäkkäitä ja makeanveden kalaa. Väitöskirjassa esitetyt tulokset, yhdessä aiemman arkeologisen materiaalin tulkinnan kanssa, lisäävät ymmärrystämme pohjoisten alueiden esihistoriallisista ruonhankintatavoista.